PERANAN LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN DALAM MEMBANTU TUGAS PEMERINTAH KELURAHAN (Studi Proses Penggalian Dan Pemanfaatan Sumber Daya Kelurahan Di Kelurahan Tanjung Rhu Kecamatan Lima Puluh Kota Pekanbaru) - Afrianda, Rendi Tri (UIR PRESS, 2018)
The study was based on the institution as a container village comunity development comunity participation in the framework of village goverment. This is very important in increasing the acceleration of development in the village. The existence of the village community empowerment in Pekanbaru city governed by a regional law number 9 of 2005 on the organization of community empowerment villages in the city of Pekanbaru. Locus in this research is quantitative method with the informant research is chairman of the village community empowerment agency Tanjung Rhu, Tanjung Rhu headman and village community leaders Tanjung Rhu. The focus of research on the function of the community empowerment villages in the excavation and utilization of institutional resources for development in the village, among others trough the implementation of the social and cultural values, strengthening the capacity of public institutions, the implementation and the results showed the role of institutions of community empowerment village still is not optimal due to budget constraints, weak institutional capacity of the village, and the village community empowerment agency participation in development planning at the moment just a deliberation development plan.